2011
DOI: 10.1302/0301-620x.93b2.24748
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of spontaneous posterior interosseous nerve palsy

Abstract: We have reviewed 38 surgically treated cases of spontaneous posterior interosseous nerve palsy in 38 patients with a mean age of 43 years (13 to 68) in order to identify clinical factors associated with its prognosis. Interfascicular neurolysis was performed at a mean of 13 months (1 to 187) after the onset of symptoms. The mean follow-up was 21 months (5.5 to 221). Medical Research Council muscle power of more than grade 4 was considered to be a good result. A further 12 cases in ten patients were treated con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 19 publications
1
46
0
1
Order By: Relevance
“…Spontaneous posterior interosseous nerve (PIN) palsy is a nontraumatic PIN palsy that has an unknown aetiology, despite careful clinical and diagnostic evaluations [1]. Space-occupying lesions are excluded from this "spontaneous" PIN (sPIN) palsy because the space-occupying lesions that can result in PIN palsy can now be diagnosed with diagnostic imaging [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spontaneous posterior interosseous nerve (PIN) palsy is a nontraumatic PIN palsy that has an unknown aetiology, despite careful clinical and diagnostic evaluations [1]. Space-occupying lesions are excluded from this "spontaneous" PIN (sPIN) palsy because the space-occupying lesions that can result in PIN palsy can now be diagnosed with diagnostic imaging [1].…”
Section: Introductionmentioning
confidence: 99%
“…Space-occupying lesions are excluded from this "spontaneous" PIN (sPIN) palsy because the space-occupying lesions that can result in PIN palsy can now be diagnosed with diagnostic imaging [1]. Thus, sPIN palsies should be distinguished from palsies that have been historically described as non-traumatic paralysis of PIN because surgical explorations of this historical condition have shown that most of the causes involved space-occupying lesions [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…He had a severe pain in his right arm, 2 weeks before the onset of the palsy. Electrodiagnostic evaluations were made, and isolated posterior interosseous nerve palsy (PINP) was conWrmed [9]. Magnetic resonance imaging of his right elbow showed no evidence of space-occupying lesion (tumour or severe synovitis).…”
Section: Case Presentationmentioning
confidence: 99%
“…Recent studies have demonstrated that age at onset, preoperative delay, complication of ulnar nerve or C8 palsy, surgical finding of fascicular constriction, and progression of palsy significantly correlate with its prognosis. 1,2) However, the therapeutic approach for incomplete spontaneous PIN palsy in which the onset occured more than a year before surgical treatment still remains controversial. Here, we present a case of spontaneous PIN palsy undergoing interfascicular neurolysis with a surgical delay of 17 years.…”
Section: Introductionmentioning
confidence: 99%